Framing Media Terhadap Konflik Keagamaan: Studi Kasus Pemberitaan Penolakan Rumah Ibadah di Kota Bekasi - Naufal Rifqi Nasution; Muhamad Noval Karom; Ahmad Sarbini; Asep Iwan Setiawan (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study analyzes how online news media frame and set the agenda on the issue of house of worship rejection in Bekasi. The research aims to understand how media construct meanings and shape public perception of religious tolerance in a multicultural society. Using a qualitative descriptive approach with content analysis, data were obtained from online articles of Detik.com, Liputan6.com, Tirto.id, and GerakanPIS.id. The findings reveal that national media emphasize administrative clarification and reconciliation, while alternative media highlight constitutional rights and social justice. Through the combination of framing and agenda-setting analysis, this study concludes that media play a dual role as a manager of public issues and a moral agent in shaping narratives of tolerance. The results contribute to the development of peace journalism in reporting religious conflicts in contemporary Indonesia.